2020
DOI: 10.3390/curroncol28010005
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Pocket Costs and Perceived Financial Burden Associated with Prostate Cancer Treatment in a Quebec Remote Area: A Cross-Sectional Study

Abstract: Background: In publicly funded healthcare systems, patients do not pay for medical visits but can experience costs stemming from travel or over-the-counter drugs. We lack information about the extent of this burden in Canadian remote regions. This study aimed to: (1) describe prostate cancer-related out-of-pocket costs and perceived financial burden, and (2) identify factors associated with such a perceived burden among prostate cancer patients living in a remote region of the province of Quebec (Canada). Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A total of 47,964,650 cancer patients participated in a total of 64 studies carried out worldwide, with study samples ranging from 26 to 19.6 million. Out of the 64 studies, 15 studies included participants with any type of cancer ( 32 , 35 , 36 , 39 , 41 , 44 , 51 , 52 , 58 , 65 , 68 , 72 , 84–86 ), a mix of 2 or more types of cancers (10 studies) ( 27 , 33 , 38 , 53 , 56 , 62 , 69 , 71 , 79 , 81 ), breast cancer (11 studies) ( 30 , 40 , 45–47 , 50 , 55 , 66 , 76 , 82 , 83 ), colorectal cancer (6 studies) ( 48 , 57 , 59 , 67 , 70 , 75 ), colon cancer ( n = 1) ( 49 ), skin cancer (3 studies) ( 20 , 77 , 78 ), lung cancer (2 studies) ( 54 , 80 ), lung cancer with brain metastasis (1 study) ( 34 ), prostate cancer (3 studies) ( 63 , 64 , 74 ), pancreatic cancer (1 study) ( 28 ), bladder cancer (2 studies) ( 29 , 31 ), head and neck cancers ( n = 3 studies) ( 43 , 60 , 61 ), blood cancer (3 studies) ( 24 , 26 , 73 ), liver cancer (1 study) ( 42 ), gynecologic cancer (1 study) ( ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 47,964,650 cancer patients participated in a total of 64 studies carried out worldwide, with study samples ranging from 26 to 19.6 million. Out of the 64 studies, 15 studies included participants with any type of cancer ( 32 , 35 , 36 , 39 , 41 , 44 , 51 , 52 , 58 , 65 , 68 , 72 , 84–86 ), a mix of 2 or more types of cancers (10 studies) ( 27 , 33 , 38 , 53 , 56 , 62 , 69 , 71 , 79 , 81 ), breast cancer (11 studies) ( 30 , 40 , 45–47 , 50 , 55 , 66 , 76 , 82 , 83 ), colorectal cancer (6 studies) ( 48 , 57 , 59 , 67 , 70 , 75 ), colon cancer ( n = 1) ( 49 ), skin cancer (3 studies) ( 20 , 77 , 78 ), lung cancer (2 studies) ( 54 , 80 ), lung cancer with brain metastasis (1 study) ( 34 ), prostate cancer (3 studies) ( 63 , 64 , 74 ), pancreatic cancer (1 study) ( 28 ), bladder cancer (2 studies) ( 29 , 31 ), head and neck cancers ( n = 3 studies) ( 43 , 60 , 61 ), blood cancer (3 studies) ( 24 , 26 , 73 ), liver cancer (1 study) ( 42 ), gynecologic cancer (1 study) ( ...…”
Section: Resultsmentioning
confidence: 99%
“…In total, 30 studies provided data on subjective FT ( 24–27 , 29 , 31 , 32 , 37 , 39 , 41 , 44–46 , 49–52 , 58 , 59 , 61 , 62 , 64 , 67–69 , 71 , 73 , 75 , 80 , 85 ). The measures of FT varied widely among the studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, 50% of patients said they had incurred treatment-related absences from work. 19 In a similar study conducted in Ontario, 35.6% of patients reported that others within their support network were required to take time off from their employment to provide them with assistance, and 20% also reported that their expenses were ‘significant and unmanageable’. 20 All these factors would undoubtedly result in greater financial hardship in individuals who are in the lower income quintile in this study.…”
Section: Discussionmentioning
confidence: 97%